Reinventing the Colonial Gaze Employing AI: a Case Study - Koutsomichalis, Marinos (My University, 2022)
This short paper accounts for a case study of artistic research revolving around Cyprus’ colonial past and inspired by present day decolonial affairs. The endeavour pivots on a hybrid AI system, trained on text from colonial handbooks of Cyprus (originally published when Cyprus was still part of the British Empire) and employing a custom image dataset meant to reflect this colonial view of the island. AI then generates new colonial ‘gazes’ of Cyprus upon demand. Output text and imagery is used in a number of physical and digital artefacts and events that are presented herein
Keywords: Digital Colonialism; Decolonisation; GAN; Text to Image Synthesis; Text Synthesis